2020
DOI: 10.3389/fphar.2020.00568
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Suppresses Proliferation and Inflammatory Cytokine Production of Synovial Fibroblasts from Rheumatoid Arthritis Patients Induced by TNF-α and Attenuates the Inflammatory Response in AIA Mice

Abstract: Rheumatoid arthritis (RA) is a chronic and progressive autoimmune disease in which activated RA fibroblast-1ike synoviocytes (RA-FLSs) are one of the main factors responsible for inducing morbidity. Previous reports have shown that RA-FLSs have proliferative features similar to cancer cells, in addition to causing cartilage erosion that eventually causes joint damage. Thus, new therapeutic strategies and drugs that can effectively contain the abnormal hyperplasia of RA-FLSs and restrain RA development are nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 66 publications
3
25
0
Order By: Relevance
“… 35 Therefore, repressing of FLS proliferation and inducing of cell apoptosis are considered to be a useful strategy for the treatment of RA. 36 , 37 In present study, our in vitro experiments results showed that NBTL could significantly induced cell apoptosis and hindered proliferation of FLS isolated from RA rat, which is consistent with the results of animal experiments in vivo . It also suggested that NBTL might play its therapeutic effect on rheumatoid arthritis through facilitating apoptosis and restraining proliferation of FLS.…”
Section: Discussionsupporting
confidence: 90%
“… 35 Therefore, repressing of FLS proliferation and inducing of cell apoptosis are considered to be a useful strategy for the treatment of RA. 36 , 37 In present study, our in vitro experiments results showed that NBTL could significantly induced cell apoptosis and hindered proliferation of FLS isolated from RA rat, which is consistent with the results of animal experiments in vivo . It also suggested that NBTL might play its therapeutic effect on rheumatoid arthritis through facilitating apoptosis and restraining proliferation of FLS.…”
Section: Discussionsupporting
confidence: 90%
“…However, we are not aware of studies that correlates this to the remaining pain observed in subsets of patients. Moreover, we did not observe an anti-inflammatory effect of T06 as previously reported [38], which could be a model or treatment time-dependent difference. Nonetheless, our data show that two osteoclast inhibitors attenuated refractive hypersensitivity in the CAIA model without affecting joint inflammation.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, RA patients treated at clinic with Tan IIA showed significant improvements in their clinical symptoms. After exploring, a researcher found that Tan IIA could effectively inhibit the increased mRNA expression of multiple matrix metalloproteinases (including MMP2, MMP3, MMP8, and MMP9) and proinflammatory factors in RA-FLSs stimulated by induced by TNF-α, resulting in the inhibition of inflammatory reactivity and end of knee joint destruction, which indicates the promising therapeutic role in the treatment of RA and shows potential to improve the life quality of RA patients ( Du et al, 2020 ). Besides, Celastrol, Ikarisoside, and AKBA (mastic acid active ingredient) suppress the activity of MMP9, one of the transcription factor NF-κB-mediated genes ( Choi et al, 2010 ; Xiao et al, 2018 ).…”
Section: Therapeutic Enzymes and Their Derivatives In Ramentioning
confidence: 99%